Ultra-Fast Middle-Up Reversed Phase Liquid Chromatography Analysis of Complex Bispecific Antibodies Obtained in Less Than One Minute - Amarande Murisier; Valentina D'Atri; Sebastian Pirner; Vincent Larraillet; Szabolcs Fekete; Matthew Lauber; Davy Guillarme (MDPI AG, 2022)
This work illustrates the benefits and limitations of using ultra-short reversed phase liquid chromatography (RPLC) columns for the characterization of various complex bispecific antibodies after prolonged thermal stress at the middle-up level of analysis. First, we have demonstrated that alternative organic modifiers, such as isopropanol, can be used in RPLC mode without generating excessive pressure, thanks to the prototype 10 × 2.1 mm, 2.7 µm particle column. However, compared to acetonitrile, the selectivity was not improved, at least for the selected biopharmaceutical products. Importantly, very fast separations (sub-1 min) of high quality were systematically obtained for the different samples when using a spectroscopic detector, but a severe loss of performance was observed with mass spectrometry (MS) detection due to dispersion effects. Based on these results, there is a clear need to improve the interfacing between LC and MS (shorter/thinner tubing) to mitigate band broadening.